ANALYSIS OF POLICY IMPLEMENTATION IN THE ONE DOOR FAMILY DATA COLLECTION PROGRAM THROUGH THE CARIK JAKARTA APPLICATION IN DASAWISMA KELURAHAN UJUNG MENTENG EAST JAKARTA DKI JAKARTA - Tuswoyo; Ahmad Hidayat; Tika Amalia Rahmah (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
The background of this research is the complaints of dasawisma cadres about the Carik Jakarta application and the low understanding of the community in operating the application on mobile phones. The Carik Jakarta application itself often experiences disturbances so that it is not optimal in collecting data. This study uses a qualitative research method with a descriptive approach through observation, interviews, and documentation. Interviews were conducted with five sources, namely the secretary of TP-PKK, RW 003 coordinator, RT 012 coordinator, dasawisma cadres, and residents of Ujung Menteng Urban-Village. Data analysis was carried out through the stages of data reduction, data presentation, and data verification. The results showed that the one-stop family data collection in the dasawisma program of Ujung Menteng Urban-Village had been running smoothly, especially in terms of resources, communication, and bureaucratic structure. However, residents are still reluctant to participate. Their enthusiasm needs to be increased to make this one-stop family data collection program a success. The obstacles that arise in the community are the refusal to be recorded, the community is difficult to communicate with and they are afraid that their personal data will be misused. In addition, using the system or server at the same time is also a challenge in itself because it hampers data collection through the Carik Jakarta application. Efforts that need to be made are to conduct campaigns to the community in detail, and continuously approach them.